Ethiopia: An agrarian economy in transition - Yared Seid; Alemayehu Seyoum Taffesse; Seid Nuru Ali (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
Ethiopia has experienced rapid economic growth since 2005. Real gross domestic product (GDP) grew at an average rate of 10.5 per cent per annum for the period between 2004-05 and 2013-14. Public investment in key infrastructure and interventions in the agriculture sector have made important contributions to GDP growth. This growth has been accompanied by a process of capital deepening and signs of structural shift away from traditional and primary sectors towards secondary and tertiary sectors. Both processes of high growth and structural shift have important implications for poverty reduction and income distribution. One potential channel through which these influences work is the labour market. The indications of structural transformation that Ethiopia has shown in the last decade, including a continuous decline in the role of agriculture and rise in that of services, have led to reallocation of jobs and labour from low-productivity agriculture to more productive industrial - in particular the construction sub-sector - and service sectors. The rise in total factor productivity, overall increase in labour force participation rate, and fall in the labour share of the agriculture sector are indicative of the nature and extent of structural shift in the Ethiopian economy. A more durable shift of economic activities towards the manufacturing sector is expected to follow the rising trend in investment in the sector. This study explores the impact of the high economic growth and slow but unmistakable structural change on a number of economic outcomes working through the labour market. The growth opportunities and challenges of the Ethiopian economy are also discussed.
Keywords: I25; O10; O12; 330; economic growth; structural transformation; labour market; Ethiopia